Issues of Moral Education in the Work of “Awrif Ul-Maarif” by Shihobiddin Umar Suhrawardi - Murtozoev Shahobiddin Bakhriddinovich (Researchparks Publishing, 2023)
In this article, the philosophical views of Abu Hafs Umar Suhrawardi, one of the major representatives of the teachings of sufism and Eastern philosophy, the founder of the Suhrawardiya order, on the understanding of the human moral it was analyzed on the basis of the work “Avoriful-maorif” (“Presents of enlightenment”). Also, the work covers the role of the sufis scholar’s ideas about the description of moral, about the education of moral in the upbringing of the young generation.